The Effect of the Immunostimulatory "Fitovak" on the Growth and Development of the Root System of Mung Bean (Eurasian Research Bulletin, 2023)
This article examines the effect of the immunostimulator "Fitovak" on mung bean root system. Three different standards of the immunostimulator "Fitovak" were obtained. From here, the development and formation of the root system was observed on the variant of applying 500 ml/t before pre-sowing and 500 ml/ha using different periods (2–4 true leaves, shading, flowering).